2015
DOI: 10.4103/2230-8210.131762
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase C-106T gene polymorphism in type 2 diabetics with microangiopathy in Iranian individuals

Abstract: Background:Aldose reductase (AR) is the rate-limiting enzyme in the glucose metabolism, which has been implicated in the pathogenesis of diabetic microvascular complications (MVCs). Frequent C-106T polymorphism in the promoter of the AR gene may change the expression of the gene.Aims:The aim of the following study is to study the association between AR C106T genotypes and diabetic MVCs in Iranian population.Materials and Methods:We included 206 type 2 diabetic patients categorized into two groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…AR converts glucose to sorbitol in the polyol pathway; 14 sorbitol cannot cross cell membranes but can accumulate in insulin-independent tissues, where it draws in water and produces osmotic stress. 15 Multiple studies have reported conflicting results regarding a potential association between AKR1B1 and DR. 16 26 For example, the C(−106)T polymorphism was significantly associated with DR in a series of 206 Iranian patients with type 2 diabetes ( P =0.03) 27 but not in a series of 268 Chinese patients with type 2 diabetes. 28 A meta-analysis of 7,831 patients from 17 studies from Asia, South America, Europe, and Australia reported a significant association between the C(−106)T polymorphism and DR in patients with type 1 diabetes (odds ratio [OR] =1.78, 95% confidence interval [CI] =1.39–2.28) but not type 2.…”
Section: Well-studied Candidate Genesmentioning
confidence: 91%
“…AR converts glucose to sorbitol in the polyol pathway; 14 sorbitol cannot cross cell membranes but can accumulate in insulin-independent tissues, where it draws in water and produces osmotic stress. 15 Multiple studies have reported conflicting results regarding a potential association between AKR1B1 and DR. 16 26 For example, the C(−106)T polymorphism was significantly associated with DR in a series of 206 Iranian patients with type 2 diabetes ( P =0.03) 27 but not in a series of 268 Chinese patients with type 2 diabetes. 28 A meta-analysis of 7,831 patients from 17 studies from Asia, South America, Europe, and Australia reported a significant association between the C(−106)T polymorphism and DR in patients with type 1 diabetes (odds ratio [OR] =1.78, 95% confidence interval [CI] =1.39–2.28) but not type 2.…”
Section: Well-studied Candidate Genesmentioning
confidence: 91%
“…An Iranian study showed that the C106T polymorphism in the ALR2 gene is a potential risk factor for the development of a retinal microvascular complication of diabetes in their population. [ 6 ] Studies on English population demonstrated the same association but in Type 1 diabetic patients. [ 5 ] Studies on Chinese patients with Type 2 diabetes showed both a significant and a nonsignificant association of C106T polymorphism of the ALR2 gene with retinopathy.…”
Section: Discussionmentioning
confidence: 77%
“…[ 1 2 ] Poor glycemic control affects both the development and progression of diabetic retinopathy (DR). [ 3 ] Family history of genetic polymorphisms in several genes including aldose reductase gene (ALR2) increases diabetic complications risk suggesting that genetic factors may also play a role in the pathogenesis of DR.[ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that high-glucose flux via AR pathway in hyperglycemia triggers alteration of glucose metabolism,[ 37 ] and vascular perturbation, leading to prothrombotic and pro-inflammatory responses in diabetic atherosclerosis,[ 38 ] and high AR expression in mice accelerates diabetic atherosclerosis both globally and in endothelial cells. [ 39 ] Results from various cellular and animal models representing a number of inflammatory conditions suggested that inflammation induced by oxidative stress which is a major contributor to diabetic complications could be reduced by the inhibition of AR which can be used for future treatment.…”
Section: Discussionmentioning
confidence: 99%